2007
DOI: 10.1242/jcs.003566
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ and cofilin activation affects peripheral actin reorganization and cell-cell contact in cells expressing integrin α5 but not its tailless mutant

Abstract: SummaryPKC␦ and cofilin activation affects peripheral actin reorganization and cell-cell contact in cells expressing integrin ␣5 but not its tailless mutant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
(70 reference statements)
0
17
1
Order By: Relevance
“…Furthermore, we show that each step of ␤ 1 integrin-mediated signaling leading to the activation of the downstream targets (20) is crucial for EBV entry into B cells. Very importantly, activation of memory B cells from peripheral blood with CD40L plus anti-IgM resulted in a vigorous upregulation of ␤ 1 integrin expression.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we show that each step of ␤ 1 integrin-mediated signaling leading to the activation of the downstream targets (20) is crucial for EBV entry into B cells. Very importantly, activation of memory B cells from peripheral blood with CD40L plus anti-IgM resulted in a vigorous upregulation of ␤ 1 integrin expression.…”
Section: Discussionmentioning
confidence: 84%
“…PKC-␦ isoform differentially regulates secretion in many cells. 9,14,34 This isoform positively regulates PAR-mediated dense granule secretion, whereas it negatively regulates GPVI-mediated dense granule secretion. In the current study, we investigated the mechanism of such differential regulation of platelet-dense granule secretion by PKC-␦.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we demonstrate that a fraction of PKCδ localizes to cellcell junctions, where it exerts a suppressive effect on the function of E-cadherin. Accordingly, it has recently been reported that activation of PKCδ is involved in the regulation of peripheral actin organization and cell-cell contacts in the epithelium (Oh et al, 2007). In addition, PKCδ has been implicated as modulating tight junctions (Mullin et al, 1998;Eckert et al, 2005).…”
Section: Discussionmentioning
confidence: 99%